Development of Android-Based Interactive Media Articulate Storyline 3 in the Merdeka Curriculum - Resi Ananda; Hadiyanto Hadiyanto; Yeni Erita; Yeni Karneli (Postgraduate, University of Mataram, 2023)
Media to increase the activities and learning outcomes of class IV students in the merdeka curriculum. The research uses the ADDIE development model with the steps of analysis, design, development, implementation, and evaluation. The validation test uses a validation questionnaire instrument, and the practicality test uses a teacher and student response questionnaire, testing the effectiveness using the pre-test and post-test instruments. In the effectiveness analysis using the One Group Pretest-Posttest Design from a predetermined group and data processing using the app's application. The research provides data results in the form of teaching module validation results obtained a value of 93.30% (very valid), material validation results of 91.55% (very valid), language validation of 94 % (very valid), and media validation of 96 % (very valid ). Based on the results of the small group practicality test response questionnaire of 93 %, the limited group obtained a score of 90.27% (very practical). Individual test results were 88.51 % (very practical) and practicality test based on teacher responses 91% (very practical). In the effectiveness test using the N-Gain Score test, the score for classes using Articulate Storyline media obtained an average of 67.2815 or 67.28%, including being effective in improving student learning outcomes.